The effect of classical music on balance, emotional state, and perceivedeffort in precompetitive artistic gymnasts and trampoline athletes - Dallas, George; Dallas, Costas; Stavropoulou, Eleni; Toli, Dimitra (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. In artistic gymnastics (AG) and trampoline (TR), athletes must be able to combine strength, flexibility, and artistry.The purpose of the study was to examine the effect of classical music on balance, emotional state, and perceived effort inprecompetitive AG and TR athletes after a 6-week intervention training program.Methods. The sample consisted of 36 athletes (20 AG and 16 TR athletes) who were randomly divided into two equalgroups: experimental (with music) and control (without music). Balance ability was assessed with the Balance Error ScoringSystem (static balance) and the Y-balance test (dynamic balance). Before and after the intervention, participants completedthe RPE-FS questionnaire which included a perceived fatigue scale (PFS) and an emotion scale (ES) to assess perceived fatigue(PF) and emotional state. The total sample followed a 6-week intervention training program, twice per week. TR athletesperformed all exercises on a TR, whereas AG athletes performed their exercises on the floor. During the 6 weeks, the athletescompleted the questionnaire before and after each training session.Results. The results showed a statistically significant improvement in static and dynamic balance in female athletes of bothsports (p < 0.05), with the percentage of improvement in AG athletes being comparatively higher than that of TR athletes.There were also significant differences in individual measures of emotional state and perceived fatigue in the examined sample.Conclusions. Classical music differentiates the rate of performance improvement in precompetitive young female athletesin these two sports.
Keywords: balance; emotional state; perceived fatigue; trampoline; artistic gymnastics